A complete description of Mitracarpus diversifolius (Rubiaceae) reveals new characters for the genus - Núñez Florentín, Mariela (2017)
Fil: Núñez Florentín, Mariela. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.